Implementasi pendekatan Design Thinking pada proses desain antarmuka pengguna (UI/UX) Aplikasi Peep Club.id menggunakan Figma - Adam Naufal Yahya, Ananda; Imam Agung, Achmad (Inovate, 2023)
Peep Club.id is a thrift shop fashion company that was founded in 2021. Jackets, jeans, sweaters, and other items are available at the store. Customers in Denpasar can place orders via social media sites such as Instagram and WhatsApp. However, because clients must use two different programs to make a purchase, using both of these platforms for transactions might be difficult. To address this issue, an appropriate solution is required, and one possible approach is to construct a user experience and user interface grand design for a sales application. The user interface is an important aspect of a mobile application since it should give consumers with comfort and ease of use. This study employs the design thinking method, which is defined as a thorough thought process focused on producing solutions that begin with empathizing with specific demands that are centered on humans (human-centric) and progress to sustainable innovation based on user needs. Empathize, Define, Ideate, Prototype, and Test are the five stages of this approach. The researcher employed the System Usability Scale (SUS) approach to conduct testing. The Peep Club.id Online Thrift Shop mobile application prototype is the product of this research. The average SUS score achieved from prototype testing using the System Usability Scale (SUS) was 79.857. It is possible to infer that the Peep Club.id Online Thrift Shop application is eligible since it fits the approval criteria Keywords: Design Thinking, Prototype, Thesis Topics.